2017
DOI: 10.3390/mi8070214
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Tool System for Lowering Friction during the Ejection of In-Die Sintered Micro Gears

Abstract: The continuous improvements in micro-forging technologies generally involve process, material, and tool design. The field assisted sintering technique (FAST) is a process that makes possible the manufacture of near-net-shape components in a closed-die setup. However, the final part quality is affected by the influence of friction during the ejection phase, caused by radial expansion of the compacted and sintered powder. This paper presents the development of a pre-stressed tool system for the manufacture of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…They also refer to the internal structure [14][15][16], which affects the quality of the surface and cracking mechanisms [17,18]. Scale effect concerns even the construction of machines [19], tooling [20,21], and tools [22][23][24][25][26], as well as the design of the technological process plan [27,28]. Materials and friction tests using microsamples are also created because their results differ from those obtained in macrotests [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…They also refer to the internal structure [14][15][16], which affects the quality of the surface and cracking mechanisms [17,18]. Scale effect concerns even the construction of machines [19], tooling [20,21], and tools [22][23][24][25][26], as well as the design of the technological process plan [27,28]. Materials and friction tests using microsamples are also created because their results differ from those obtained in macrotests [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The size of the grain affects the geometric characteristics of the product, such as the shape and quality of the surface [17], but above all affects the functional properties [18][19][20][21]. The scale effect is also applied to the construction of machines [22], instrumentation [23,24], tools [25][26][27], and technological plans [28][29][30]. Materials and friction tests using microsamples are also created because their results differ from those obtained in macrotests [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Process developments of micro-scale fabrication methods. Cannella et al [1] developed a novel tooling system for in-die sintering of micro metal gears; Martinez-López et al [2] investigated xurography and laser ablation processes for the rapid fabrication of micromixing arrays; Obikawa et al [3] demonstrated ultrasonic-assisted incremental microforming for the rapid prototyping of thin shell metal pyramids. (2) Micro/nano manufacturing technologies based on electrochemical processing.…”
mentioning
confidence: 99%